DIGITAL PLATFORMS AND GLOBALIZATION OF PERFORMING ARTS - Arivukkodi R; Anitha M; Sivasankari V; Kuppusamy, Baskaran; Durga B; Srimathi N (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The rapid advancement of digital technologies has significantly transformed the landscape of performing arts, enabling unprecedented levels of global connectivity and audience engagement. Digital platforms such as streaming services, social media networks, and virtual performance spaces have redefined how performing arts—including theatre, dance, and music—are produced, distributed, and consumed worldwide. This globalization through digitalization has allowed artists and cultural institutions to transcend geographical limitations, making performances accessible to diverse audiences across continents. As a result, digital platforms have become essential tools for cultural exchange, preservation, and innovation in the performing arts sector. This study explores the role of digital platforms in facilitating the globalization of performing arts and examines how technological advancements have reshaped artistic production, audience participation, and cultural dissemination. The research analyzes the opportunities offered by digital platforms, such as increased visibility for artists, new revenue models, and interactive audience experiences. At the same time, it addresses key challenges including digital inequality, copyright protection, authenticity of live performances, and the commercialization of cultural expressions. Furthermore, the paper investigates how performing artists and organizations adapt their creative practices to suit digital environments through hybrid and virtual performances. The study also evaluates the impact of digital globalization on cultural diversity and the preservation of traditional art forms. By examining case studies and current digital trends, this research highlights the transformative potential of digital platforms in sustaining and expanding the global reach of performing arts while maintaining cultural integrity. The findings aim to provide insights for artists, cultural institutions, and policymakers on effectively leveraging digital technologies for the sustainable development of the performing arts industry.